Measurement of inelastic, single- and double-diffraction cross sections in proton-proton collisions at the LHC with ALICE - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Constantin, Paul; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; et al. (The European physical journal. C, Particles and fields, 2013)
Measurements of cross sections of inelastic and diffractive processes in proton–proton collisions at LHC energies were carried out with the ALICE detector. The fractions of diffractive processes in inelastic collisions were determined from a study of gaps in charged particle pseudorapidity distributions: for single diffraction (diffractive mass M X <200 GeV/c 2) σSD/σINEL=0.21±0.03,0.20+0.07−0.08, and 0.20+0.04−0.07, respectively at centre-of-mass energies s√=0.9,2.76, and 7 TeV; for double diffraction (for a pseudorapidity gap Δη>3) σ DD/σ INEL=0.11±0.03,0.12±0.05, and 0.12+0.05−0.04, respectively at s√=0.9,2.76, and 7 TeV. To measure the inelastic cross section, beam properties were determined with van der Meer scans, and, using a simulation of diffraction adjusted to data, the following values were obtained: σINEL=62.8+2.4−4.0(model)±1.2(lumi) mb at s√=2.76 TeV and 73.2+2.0−4.6(model)±2.6(lumi) mb at s√=7 TeV. The single- and double-diffractive cross sections were calculated combining relative rates of diffraction with inelastic cross sections. The results are compared to previous measurements at proton–antiproton and proton–proton colliders at lower energies, to measurements by other experiments at the LHC, and to theoretical models.
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Constantin, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, K. Koch, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J.H. Stiller, J. Ulrich, S. Vallero, Y. Wang, B. Windelband, A. Zimmermann und weitere 960
Gesehen am 30.04.2021